Changing care? Men and managerialism in the nonprofit sector. (September 2015) - Baines, Donna; Charlesworth, Sara; Cunningham, Ian
Summary: The movement of men into care work in the predominantly female voluntary sector appears to be an unintended impact of welfare state contracting-out, managerialism and labour market restructuring. While not uniform, our comparative, international data (New Zealand and Scotland) show that some groups of men in nonprofit care work jobs embraced managerialism and used aspects of it to reshape and advance their work, while others undertook practices exemplifying a 'caring masculinity' more similar to practices currently associated with femininised ways of undertaking care activities. Findings: Drawing on international comparative data collected as part of a larger study of restructuring in the nonprofit social services, this article suggests analytic clusters of masculinities operating in the voluntary sector and explores how the presence of men in care work may be changing it. The article also shows how hegemonic, masculinist-oriented practices in the workplace appear more amenable to managerialism than the expected feminine self-sacrificing, self-exploiting ethos of this highly gendered, female-majority sector. Applications: These findings provide insights into the gendered and changing work in the nonprofit social services sector, and suggest ways the gender order is changing with the influx of male workers. The findings will be of interest to social work managers, supervisors, practitioners, policy analysts, students and educators.